The impact of HPV vaccination beyond cancer prevention: effect on pregnancy outcomes. Issue 10 (3rd October 2021) - Yuill, Susan; Velentzis, Louiza S.; Smith, Megan; Egger, Sam; Wrede, C. David; Bateson, Deborah; Arbyn, Marc; Canfell, Karen
ABSTRACT: While the benefits of human papillomavirus (HPV) vaccination relating to cervical cancer prevention have been widely documented, recent published evidence is suggestive of an impact on adverse pregnancy outcomes (APOs) in vaccinated mothers and their infants, including a reduction in rates of preterm births and small for gestational age infants. In this review, we examine this evidence and the possible mechanisms by which HPV vaccination may prevent these APOs. Large-scale studies linking HPV vaccination status with birth registries are needed to confirm these results. Potential confounding factors to consider in future analyses include other risk factors for APOs, and historical changes in both the management of cervical precancerous lesions and prevention of APOs. If confirmed, these additional benefits of HPV vaccination in reducing APO rates will be of global significance, due to the substantial health, social and economic costs associated with APOs, strengthening the case for worldwide HPV immunization.